(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This paper explores Søren Kierkegaard’s allegiance to ‘Divine Command Theory’ and the implications of such for our understanding of Kierkegaard as an existential philosopher. It argues that Kierkegaard’s perspective not only raises deeply troubling ethical concerns, it provides a means for distinguishing and clarifying what might be those distinctive Principles upon which existential phenomenology is founded.